Hypoxia Enhances the Angiogenic Potential of Human Dental Pulp Cells - Aranha, Andreza M. F. [UNESP]; Zhang, Zhaocheng; Neiva, Kathleen G.; Costa, Carlos A. S. [UNESP]; Hebling, Josimeri [UNESP]; Noer, Jacques E. (Elsevier B.V., 2010)
Introduction: Trauma can result in the severing of the dental pulp vessels, leading to hypoxia and ultimately to pulp necrosis. Improved understanding of mechanisms underlying the response of dental pulp cells to hypoxic conditions might lead to better therapeutic alternatives for patients with dental trauma. The purpose of this study was to evaluate the effect of hypoxia on the angiogenic response mediated by human dental pulp stem cells (DPSCs) and human dental pulp fibroblasts (HDPFs). Methods: DPSCs and HDPFs were exposed to experimental hypoxic conditions. Hypoxia-inducible transcription factor-1 alpha (HIF-1alpha) was evaluated by Western blot and immunocytochemistry, whereas vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) expression was evaluated by enzyme-linked immunosorbent assay. YC-1, an inhibitor of HIF-1alpha, was used to evaluate the functional effect of this transcriptional factor on hypoxia-induced VEGF expression. Conditioned medium from hypoxic and normoxic pulp cells was used to stimulate human dermal microvascular endothelial cells (HDMECs). HDMEC proliferation was measured by WST-1 assay, and angiogenic potential was evaluated by a capillary sprouting assay in 3-dimensional collagen matrices. Results: Hypoxia enhanced HIF-1alpha and VEGF expression in DPSCs and HDPFs. In contrast hypoxia did not induce bFGF expression in pulp cells. YC-1 partially inhibited hypoxia-induced HIF-1alpha and VEGF in these cells. The growth factor milieu of hypoxic HDPFs (but not hypoxic DPSCs) induced endothelial cell proliferation and sprouting as compared with medium from normoxic cells. Conclusions: Collectively, these data demonstrate that hypoxia induces complex and cell type specific pro-angiogenic responses and suggest that VEGF (but not bFGF) participates in the revascularization of hypoxic dental pulps. (J Endod 2010;36:1633-1637)
Keywords: Angiogenesis; dental pulp; endodontics; tissue regeneration; trauma